After the catastrophe: working with the intergenerational transmission of collective trauma in Jungian analysis. Issue 1 (13th April 2022) - Feldman, Brian
Abstract: The psychological/emotional impact of the collective traumas and psychic catastrophes of the Jewish holocaust, Stalin's Gulags, and China's Cultural Revolution upon the second and third generation of survivors in the U.S., China and Russia is explored through the lens of Jungian analysis and infant observation. Infant observation research in Russia and China provides a scaffolding for the study of the transmission of collective trauma. Parent/infant interactions that may indicate that the intergenerational transmission of trauma is taking place will be explored. Analytical and infant observation research indicate that trauma can be transmitted from one generation to the next, often unconsciously, and that the impact of collective trauma creates tears and holes in the emergent cultural and personal psychic skins of the infant that can impede the development of a coherent individual identity, as well as secure attachment relationships. These tears and holes in the cultural and personal psychic skins can later become the focus of analysis in the second and third generation of survivors. Analysis can become a space for both collective/personal mourning and healing as coherent symbolic, historical and personal narratives are co‐constructed and integrated within the analytical temenos. Abstract : Par l'angle de l'analyse Jungienne et de l'observation du nourrisson, nous étudions l'impact émotionnel/psychologique aux USA sur la seconde et troisième génération de survivants de traumatismes collectifs et de catastrophes psychiques: la Shoah, les Goulags de Staline, la Révolution Culturelle en Chine. La recherche en Russie et en Chine sur l'observation du nourrisson fournit une structure pour l'étude de la transmission du traumatisme collectif. Nous étudions les interactions parent/enfant qui peuvent indiquer qu'une transmission intergénérationnelle soit à l'œuvre. La recherche sur l'observation analytique et l'observation du nourrisson montre que le traumatisme peut être transmis d'une génération à la suivante, souvent inconsciemment, et que l'impact du traumatisme collectif crée des déchirures et des trous dans les peaux psychiques personnelles et culturelles, en cours de formation, de l'enfant. Ceci peut entraver le développement d'une identité individuelle cohérente et de relations d'attachement fiables. Ces déchirures et trous dans les peaux psychiques personnelles et culturelles peuvent par la suite devenir le point d'attention de l'analyse pour des survivants de seconde ou de troisième génération. L'analyse peut devenir un espace pour un deuil personnel et collectif et pour la guérison en co‐construisant des récits symboliquement cohérents, historiques et personnels, et en les intégrant à l'intérieur du téménos analytique. Abstract : Der psychologische/emotionale Einfluß der kollektiven Traumata und psychischen Katastrophen des jüdischen Holocaust, Stalins Gulags und Chinas Kulturrevolution auf die zweite und dritte Generation von Überlebenden in den USA, China und Rußland wird durch die Linse Jungianischer Analyse und Säuglingsbeobachtung untersucht. Die Säuglingsbeobachtungsforschung in Rußland und China bietet ein Gerüst für die Erforschung der Übertragung kollektiver Traumata. Eltern‐Kind‐Interaktionen werden untersucht die darauf hinweisen können, daß die Übertragung von Traumata zwischen den Generationen stattfindet. Analytische und Säuglingsbeobachtungsforschung weisen darauf hin, daß Traumata von einer Generation auf die nächste übertragen werden können, oft unbewußt, und daß die Auswirkungen eines kollektiven Traumas Risse und Löcher in der entstehenden kulturellen und persönlichen psychischen Haut des Säuglings erzeugen, die die Entwicklung von einer kohärenten individuellen Identität sowie sichere Bindungsbeziehungen behindern können. Diese Risse und Löcher in der kulturellen und persönlichen psychischen Haut können später in der zweiten und dritten Generation von Überlebenden zum Fokus der Analyse werden. Analyse kann zu einem Raum für kollektive/persönliche Trauer und Heilung werden, da kohärente symbolische, historische und persönliche Erzählungen mitkonstruiert und in den analytischen Temenos integriert werden. Abstract : L'impatto psicologico/emotivo dei traumi collettivi e delle catastrofi psichiche dell'olocausto ebraico, dei gulag di Stalin, e della rivoluzione culturale cinese sulla seconda e terza generazione di sopravvissuti negli Stati Uniti, in Cina e in Russia è esplorato attraverso la lente dell'analisi junghiana e l'osservazione infantile. La ricerca sull'osservazione infantile in Russia e Cina offre un'impalcatura per lo studio della trasmissione del trauma collettivo. Verranno esplorate le interazioni genitore/bambino che possono indicare che la trasmissione intergenerazionale del trauma è in atto. La ricerca analitica e l'osservazione infantile indicano che il trauma può essere trasmesso da una generazione all'altra, spesso inconsciamente, e che l'impatto del trauma collettivo crea delle lacerazioni e falle nella pelle psichica culturale e personale emergente del bambino che possono ostacolare lo sviluppo di un'identità individuale coerente, nonché legami di attaccamento sicuri. Queste lacerazioni e falle nelle pelli psichiche culturali e personali possono successivamente diventare il centro dell'analisi nella seconda e terza generazione di sopravvissuti. L'analisi può diventare uno spazio sia per il lutto collettivo/personale che per la guarigione, poiché narrazioni simboliche, storiche e personali coerenti sono co‐costruite ed integrate all'interno del temenos analitico. Abstract : Психологическое/эмоциональное воздействие коллективных травм и психических катастроф еврейского холокоста, сталинских ГУЛАГов и Культурной революции в Китае на второе и третье поколения выживших в США, Китае и России исследуется через призму юнгианского анализа и наблюдения за младенцами. Исследования по наблюдению за младенцами в России и Китае обеспечивают основу для изучения передачи коллективной травмы. Будут изучены взаимодействия родителей и младенцев, которые могут указывать на передачу травмы от поколения к поколению. Аналитические исследования и наблюдения за младенцами показывают, что травма может передаваться от одного поколения к другому, часто бессознательно, и что воздействие коллективной травмы создает разрывы и дыры в формирующейся культурной и личной психической коже младенца, что может препятствовать развитию внутренне согласованной индивидуальная идентичность, а также надежной привязанности. Эти разрывы и дыры в культурной и личной психической коже могут позже стать предметом анализа второго и третьего поколений выживших. Анализ может стать пространством как для коллективного/личного траура, так и для исцеления, поскольку в аналитическом теменосе происходит конструирование и интеграция символических, исторических и личных нарративов. Abstract : A través de la perspectiva del análisis Junguiano y de la observación infantil, se explora el impacto psicológico/emocional de traumas colectivos y catástrofes psíquicas en la segunda y tercera generación de sobrevivientes en los Estados Unidos, China y Rusia, del holocausto judío, los Gulags de Stalin y la Revolución Cultural China. Investigación en observación infantil en Rusia y China provee el andamiaje para el estudio de la transmisión de trauma colectivo. Se exploran las interacciones madre‐padre/niño‐niña que puedan indicar que la transmisión intergeneracional del trauma está teniendo lugar. Investigaciones en psicología analítica y observación infantil indican que el trauma puede ser transmitido de una generación a la siguiente, a menudo inconscientemente, y que el impacto del trauma colectivo crea desgarros y huecos en la piel psíquica cultural y personal emergente del bebé que puede impedir el desarrollo de una identidad individual coherente, así como relaciones de apego seguras. Estos desgarros y huecos en la piel psíquica cultural y personal puede luego devenir en el foco de análisis en las segundas y terceras generaciones de sobrevivientes. El análisis puede devenir en un espacio tanto para el duelo colectivo/personal, como también para la sanación a medida que narrativas simbólicas, históricas y personales son co‐construídas e integradas en el temenos analítico. Abstract : 灾难之后:在荣格分析背景下对代际集体创伤传递进行工作 文章通过荣格分析的视角及婴儿观察, 探索了集体创伤和心理灾难, 对于受害者在美国的第二代和第三代后人的心理/情绪影响。文章研究的对象来自美国、中国、和俄罗斯, 犹太集中营, 斯大林集中营, 中国文革幸存者的后人。在俄罗斯和中国的婴儿观察提供了一个研究的脚手架, 来探索集体创伤的代际传播。文章探讨了创伤代际传递可能发生在父母/婴儿互动中。分析性的婴儿观察研究显示, 创伤可能常常以无意识的方式从一代人传递给下一代人, 集体创伤在新兴的文化和婴儿个体的心理皮肤中制造了眼泪和空洞, 这会妨碍凝聚的独特自体的发展, 以及安全依恋的发生。这些文化和个体心理皮肤上的眼泪和空洞可以在后期, 出现在幸存者第二代和第三代的后人的分析中, 从而被关注。分析会作为一个凝聚的象征, 成为集体/个人的哀悼和治愈的空间, 在其中, 历史性的和个体的叙事被共同建构, 并整合到分析的圣地之中。 Abstract : O impacto psicológico/emocional dos traumas coletivos e catástrofes psíquicas do holocausto judeu, dos Gulags de Stalin e da Revolução Cultural da China na segunda e terceira geração de sobreviventes nos EUA, China e Rússia é explorado através da lente da análise junguiana e da observação infantil. A pesquisa de observação infantil na Rússia e na China fornece um andaime para o estudo da transmissão do trauma coletivo. Interações pais/bebê que podem indicar que a transmissão intergeracional do trauma está ocorrendo serão exploradas. Pesquisas analíticas e de observação infantil indicam que o trauma pode ser transmitido de uma geração para a outra, muitas vezes inconscientemente, e que o impacto do trauma coletivo cria lágrimas e buracos nas peles psíquicas culturais e pessoais emergentes do bebê que podem impedir o desenvolvimento de uma identidade individual coerente, bem como relações seguras de apego. Essas lágrimas e buracos nas peles psíquicas culturais e pessoais podem mais tarde se tornar o foco de análise na segunda e terceira geração de sobreviventes. A análise pode se tornar um espaço para luto coletivo/pessoal e cura, pois narrativas simbólicas, históricas e pessoais coerentes são coconstruídas e integradas dentro do temenos analíticos.